A note on the estimation of stochastic and deterministic production frontiers with maximum entropy - Macedo, Pedro (2019)
Stochastic frontier analysis with maximum entropy estimation has received considerable attention in the literature in the recent years. In this work, the estimation of stochastic and deterministic production frontiers with maximum entropy methods, the advantages and disadvantages relatively to maximum likelihood, and some proposals to improve maximum entropy estimation in this context are presented and discussed.